2011
DOI: 10.1097/tp.0b013e31821774e0
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Xenograft Survival Induced by Inducible Costimulator-Ig Is Associated With Increased Forkhead Box P3+ Cells

Abstract: This study demonstrates prolonged xenograft survival by local expression of ICOS-Ig, we propose that the accumulation of CD4(+)CD25(+)Foxp3(+) cells at the periphery of the graft and secretion of interleukin-10 is responsible for this novel observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
6
14
0
Order By: Relevance
“…Each buffer was used according to the manufacturer instructions. We observed that fixation/permeabilization buffers affected the SSC/FSC characteristics of the cells (Figure 1, row 1), and this result was identical to the staining results of human Treg cell (Hodgson et al, 2011). The CD3 staining was consistent, with 23 to 37% of CD3 + events in the lymphocyte gate of PBMCs and 22 to 29% in the spleen lymphocyte gate (Figure 1, row 2).…”
Section: Comparison Of Fixation/permeabilization Bufferssupporting
confidence: 72%
See 1 more Smart Citation
“…Each buffer was used according to the manufacturer instructions. We observed that fixation/permeabilization buffers affected the SSC/FSC characteristics of the cells (Figure 1, row 1), and this result was identical to the staining results of human Treg cell (Hodgson et al, 2011). The CD3 staining was consistent, with 23 to 37% of CD3 + events in the lymphocyte gate of PBMCs and 22 to 29% in the spleen lymphocyte gate (Figure 1, row 2).…”
Section: Comparison Of Fixation/permeabilization Bufferssupporting
confidence: 72%
“…+ (Hodgson et al, 2011). Several publications noted concerns about the influence of different clones of Foxp3 antibodies coupled to different fluorochromes and paired with different fixation/permeabilization buffers on the staining of human Treg cells (Tran et al, 2007;Pillai and Karandikar, 2008;Grant et al, 2009;Law et al, 2009;Presicce et al, 2010).…”
Section: Cd4mentioning
confidence: 99%
“…The in vivo infusion of hPD-L1 þ endothelial cells prolongs the survival of porcine skin grafts, favoring the expansion of Foxp3 þ CD4 þ T cells (Ding et al 2011). Much the same results have been obtained in mice by grafting porcine endothelial cells transfected with ICOS-Ig, a soluble form of ICOS (Hodgson et al 2011), suggesting that Treg-based strategies may represent a novel path toward achieving tolerance in xenotransplantation.…”
Section: T-cell Tolerance and Tregsvsupporting
confidence: 65%
“…The effects of ICOS on the functions of T cell are mainly initiated by the interaction between ICOS and its ligand (B7 related protein 1, B7RP1 or ICOSL), which is generally expressed on diverse antigen presenting cells (APC) [2]. ICOS-related signal plays important roles in many T cell-mediated disease models, such as inflammation [3], anti-viral immune responses [4], anti-tumor immune responses [5], allogeneic grafts rejection [6,7], wound healing [8], and thus representing a potential target of treatment [9]. However, the roles of ICOS-ICOSL interaction in human immune system are still inclusive.…”
Section: Introductionmentioning
confidence: 99%